Potent influence of obesity on suppression of plasma B-type natriuretic peptide levels in patients with acute heart failure: An approach using covariance structure analysis. (15th July 2016) - Kinoshita, Koji; Kawai, Makoto; Minai, Kosuke; Ogawa, Kazuo; Inoue, Yasunori; Yoshimura, Michihiro
Abstract: Background: Plasma B-type natriuretic peptide (BNP) levels may vary widely among patients with similar stages of heart failure, in whom obesity might be the only factor reducing plasma BNP levels. We investigated the effect of obesity and body mass index (BMI) on plasma BNP levels using serial measurements before and after treatment (pre- and post-BNP and pre- and post-BMI) in patients with acute heart failure. Methods: Multiple regression analysis and covariance structure analysis were performed to study the interactions between clinical factors in 372 patients. The pre-BMI was shown as a combination index of obesity and fluid accumulation, whereas the post-BMI was a conventional index of obesity. Results: There was a significant inverse correlation between BMI and BNP in each condition before and after treatment for heart failure. The direct significant associations of the log pre-BNP with the log post-BNP (β: 0.387), the post-BMI (β: − 0.043), and the pre-BMI (β: 0.030) were analyzed by using structural equation modeling. The post-BMI was inversely correlated, but importantly, the pre-BMI was positively correlated, with the log pre-BNP, because the pre-BMI probably entailed an element of fluid accumulation. There were few patients with extremely high levels of pre-BNP among those with high post-BMI, due to suppressed secretion of BNP. Conclusions: The low plasma BNP levels in true obesity patients with acute heart failure are of concern, because plasma BNP cannot increase in such patients. Highlights: Obesity might be the only factor reducing plasma BNP levels. Pre-BMI was positively correlated with the log pre-BNP. The pre-BMI probably entailed an element of fluid accumulation. High plasma BNP levels in obese with heart failure might not reflect true obesity. Low plasma BNP levels are of concern in heart failure in true obesity.